ANALYSIS OF ACTUAL AND INTENDED DESTINATION CHOICE PATTERNS OF CANADIAN IMMIGRANTS - Young, Jennifer M. (My University, 1989)
The overall theme of this study is an analysis of the actual and intended destination choice patterns of Canadian immigrants who landed during the 1970s . Actual destination choice patterns are described using data from the 2% Public Use Sample of the 1981 Census. I ntended destination choice patterns are described using annual tallies of the Department of Employment and Immigration (1971 - 1981). Four main issues are considered.
First, the pattern of actual destination choice for the 1970s is described. The Atlantic was the least favoured destination, although it received higher than average proportions of young, well-educated and professional immigrants . Quebec increased in popu lar i ty toward the end of the decade, particularly for immigrants from countries other than Britain and the United states. Ontario remained the most popular destination, although its attractiveness declined during the oil boom, when that of Alberta and the Prairies rose commensurately. British Columbia continued to attract a disproportionately large share of immigrants, particularly British, Asian and elderly.
Second, the intended destination choice pattern is described and compared with the actual pattern. Ontario displays the best correspondence. The Atlantic shows the poorest correspondence, however, as the intended choice proportion exceeds the actual proportion by a wide margin.
This excess, though smaller, also appears in Quebec and the Prairies. In contrast, the actual share exceeds the intended share in Alberta and British Columbia.
Third, the gap between intended and actual destination choice proportions is examined for systematic divergence. The gap appears to be narrow in the years just prior to the census, and appears to diverge somewhat in earlier years. Very popular and very unpopular destinations, such as Alberta and the Atlantic, demonstrate comparatively larger gaps than destinations of average popularity.
Fourth, logit analysis concludes that ecological variables and interaction terms involving ecological and personal variables were significant in explaining the actual destination choices. Coldness had a negative effect on destination choice, whereas relative population size, ethnic concentration, wage rate and employment growth had positive effects. The statistically significant interaction terms indicate, among other things, that Asians and Southern Europeans had a stronger preference for destinations with high concentrations of ethnically similar populations. The application of the logit model to the intended destination choice data yields a similar result: all ecological variables and the interactions between ethnic concentration and Asian and Southern European immigrants remain highly significant.
Keywords: Geography; Geography